Authors, authorship order, the moving finger writes - Jayakumar Avula; Haritha Avula (Wolters Kluwer Medknow Publications, 2015)
There has been a phenomenal increase in the number of research papers with multiple authors. Increasing academic pressures and halo around individuals with prolific publications have made many aspirants to claim authorship. Increasing number of authors has brought its own issues of author credits, disputes, rivalry, and a degree of unwelcome scramble for credit sharing. Many unresolved issues about authorship and various guidelines and admonitions are more often infringed than adhered to. The position of the first and last author seem to be well recognized in medical and dental journals, but the fate of middle authors is left to guessing and often of inconsequential importance. Most of these issues, as well as fraud, misconduct in medical research publications, have been discussed amply but too of no avail. It is comforting to know that except for small shouts and whispers, dental research has been relatively free from scams and frauds. The complacency, however, needs to be tempered with constant vigil against fraud, falsification and fabrication of research reports. Honest authorship, vigilant editors, robust peer review, and a discerning readership are the sine qua non for a good research paper. Academic institutions and selection committees should be concentrating on the quality of research papers and not enamored of their number.